1989
DOI: 10.1017/s0068246200009144
|View full text |Cite
|
Sign up to set email alerts
|

The food refuse of an affluent urban household in the late fourteenth century: faunal and botanical remains from the Palazzo Vitelleschi, Tarquinia (Viterbo)

Abstract: RIFIUTI ALIMENTARI DI UNA RICCA FAMIGLIA CITTADINA NEL TARDO SECOLO QUATTORDICESIMO: RESTI FAUNISTICI E BOTANICI DAL PALAZZO VITELLESCHI, TARQUINIA (VITERBO)Gli scavi condotti dalla British School at Rome nel Palazzo Vitelleschi in Tarquinia hanno fornito una quantità considerevole di dati faunistici e botanici, molti dei quali relativi al “proto-palazzo” del tardo sec. XIV. Le analisi del materiale qui presentate permettono di ricostruire in maniera abbastanza dettagliata il regime alimentare di una ricca e p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The first studies to use genome-wide data found that R. norvegicus moved out of China into southeast Asia from which it became a truly global menace a few hundred years ago when brown rats were moved all over the world by European colonial powers (Puckett et al 2016). Molecular data used in coalescent models estimated European rats diverged approximately 1227 AD (90% Highest Density Probability (HDP): 589-1781 AD) (Puckett and Munshi-South 2019); this time frame was congruent with brown rat archeological remains found in Tarquinia, Italy where the site was dated from 1390-1436 (Clark et al 1989).…”
Section: Introductionmentioning
confidence: 54%
“…The first studies to use genome-wide data found that R. norvegicus moved out of China into southeast Asia from which it became a truly global menace a few hundred years ago when brown rats were moved all over the world by European colonial powers (Puckett et al 2016). Molecular data used in coalescent models estimated European rats diverged approximately 1227 AD (90% Highest Density Probability (HDP): 589-1781 AD) (Puckett and Munshi-South 2019); this time frame was congruent with brown rat archeological remains found in Tarquinia, Italy where the site was dated from 1390-1436 (Clark et al 1989).…”
Section: Introductionmentioning
confidence: 54%
“…According to the archaeozoological record, the most recent finds are comprised between the 12th and the 15th centuries (Clark 1989, Riedel 1994, Baker 2007. A few literary references, mainly Amatus Lusitanus (1553) and Aldrovandi (1637), suggest that the last Italian beaver populations resisted in Polesine (the easternmost area of the Po Plain) between the mid 16th century and the beginning of the 17th century.…”
Section: Discussionmentioning
confidence: 99%
“…According to historical texts (Le Glay, 1975;Fourquin, 1975), most archaeobotanical and sedimentological (Brochier, 1983) analyses detected the major deforestation phase between the 9th and the 13th centuries  [Eastern Spain (Planchais & Parra Vergara, 1984;Riera-Mora & Esteban-Amat, 1994), Dordogne (Diot & Laborie, 1989), Roussillon (Planchais, 1985), Languedoc (Durand & Vernet, 1987;Chabal, 1991;Durand, 1991Durand, , 1992, French Alps (Colardelle & Vedrel, 1993), Puglia (Martin, 1984), Sicily (Bossard-Beck, 1984: 645)]. Data on this topic are peculiarly scarce from the area around the Tyrrhenian Sea (Barker & Hodges, 1981;Clark et al, 1989).…”
Section: T He Landscapes Of Western Mediterraneanmentioning
confidence: 99%